Importance of international networking in academic family medicine - Zalika Klemenc-Ketiš; Janko Kersnik (Acta Medica Academica, 2014)
European family medicine/general practice (FM/GP) has travelled the long and successful journey of profiling the discipline and has produced valuable position papers on education and research. Nowadays, academic medicine is one of the pillars in the future development of FM/GP in Europe. A common European curriculum on undergraduate and postgraduate family medicine is needed. Also, a sound international platform of teaching institutions and/or teachers of family medicine would foster the further development of family medicine as an academic discipline. This would stimulate students and teachers to engage in international exchange to gain new knowledge and experiences, present their work and ideas abroad and prepare the conditions for further exchange of students and teachers. Conclusion. Established departments of FM/GP, led by a teacher who is a family physician/general practitioner, at each Medical School in Europe should provide students with knowledge and skills related to the core attributes of FM/GP. International exchanges of teachers and students should foster the development of a common curriculum on FM in Europe and foster improvement in the quality of FM education.